The ammonium transporter AmtB and the PII signal transduction protein GlnZ are required to inhibit DraG in Azospirillum brasilense. (12th February 2019) - Moure, Vivian R.; Siöberg, Catrine L. B.; Valdameri, Glaucio; Nji, Emmanuel; Oliveira, Marco Aurelio S.; Gerdhardt, Edileusa C. M.; Pedrosa, Fabio O.; Mitchell, David A.; Seefeldt, Lance C.; Huergo, Luciano F.; Högbom, Martin; Nordlund, Stefan; et al.
Abstract : The ammonium‐dependent posttranslational regulation of nitrogenase activity in Azospirillum brasilense requires dinitrogenase reductase ADP‐ribosyl transferase (DraT) and dinitrogenase reductase ADP‐glycohydrolase (DraG). These enzymes are reciprocally regulated by interaction with the PII proteins, GlnB and GlnZ. In this study, purified ADP‐ribosylated Fe‐protein was used as substrate to study the mechanism involved in the regulation of A. brasilense DraG in vitro . The data show that DraG is partially inhibited by GlnZ and that DraG inhibition is further enhanced by the simultaneous presence of GlnZ and AmtB. These results are the first to demonstrate experimentally that DraG inactivation requires the formation of a ternary DraG‐GlnZ‐AmtB complex in vitro . Previous structural data have revealed that when the DraG‐GlnZ complex associates with AmtB, the flexible T‐loops of the trimeric GlnZ bind to AmtB and become rigid; these molecular events stabilize the DraG‐GlnZ complex, resulting in DraG inactivation. To determine whether restraining the flexibility of the GlnZ T‐loops is a limiting factor in DraG inhibition, we used a GlnZ variant that carries a partial deletion of the T‐loop (GlnZΔ42‐54). However, although the GlnZΔ42‐54 variant was more effective in inhibiting DraG in vitro, it bound to DraG with a slightly lower affinity than does wild‐type GlnZ and was not competent to completely inhibit DraG activity either in vitro or in vivo . We, therefore, conclude that the formation of a ternary complex between DraG‐GlnZ‐AmtB is necessary for the inactivation of DraG. Abstract : To gain insights into the mechanism of the regulation of dinitrogenase reductase ADP‐glycohydrolase (DraG), we have investigated the functional significance of the formation DraG‐GlnZ and DraG‐GlnZ‐AmtB complexes. We conclude that the formation of the ternary DraG‐GlnZ‐AmtB complex is required for the full inhibition of Azospirillum brasilense DraG toward its natural substrate, ADP‐ribosylated Fe‐protein.